Experimental and Analytical Study of the Novel Static Flow Meters - (:unkn) unknown (My University, 2019)
Flow metering is the measurement of the volume of a substance passing through a cross-sectional area per unit time. In various industries, many diverse types of flow meters are used to evaluate and control the velocity of the fluid passing through a system. In the water industry, flow meters are crucial in evaluating the performance of large scale industrial water filtration systems, and in the detection of underperforming elements. Reliable flow metering technology is essential to guarantee the production of clean safe drinking water. An ongoing issue with existing flow metering technologies is cost-effectiveness. This is a major limiting factor for widespread use. One of the focuses of this research was expense reduction of the system and the final product. The end goal was to create and validate designs for low cost static, and robust flow sensors. The objective of this project was to design a simple, easily manufactured flow meter with no moving parts. By reducing the cost, precision is sacrificed in some aspects, however, the design still proved to be a viable substitution. Differential pressure flow metering was selected based on target and orifice plate meters to generate the main idea of the project. Simple designs were pursued utilizing strain gauges and basic data acquisition systems, and ultimately three designs were created. The general design methodology involved mounting a strain gauge on a custom designed laser cut Acrylic plate, and inserting it as a pipe cross section to target water flow. For each design equations were analytically derived and specimens were created with varying geometric parameters. A multi-level factorial analysis was performed on each design to identify which geometric properties were critical to flow sensitivity. Three variables (thickness, length, width) for each design were studied based on the derived equations. Based on the results, the thickness of the designed plate was the most effective parameter in ensuring accuracy. Lower thickness leads to a more sensitive system and better results. Width and Length of the cut area on which strain gauge was mounted were other geometric properties thoroughly studied. Designs were developed that were found to be inert to certain potential manufacturing variation through analytical analysis with experimental validation. Beam bending was a critical component to all the designs created. One design was created that measured flow independent of beam width, and another was created which produced results independent of beam length. Across all designs, sensitivity and flow measurement were highly sensitive to the thickness of the beam.
Keywords: factorial analysis; flow meter; sensing technology; strain gauge